O ‘Selfie’! O Narcissus: The Mythologico-cultural Imposition of Late-capitalistic Tools in the Present Digital World (Global Journal of Human-Social Science, 2022)
The paper propounds that the late-capitalistic tools were imposed in the once-colonialized countries through establishing a myth in the arena of Cell phones The paper taking only individual selfies into account endeavours to discover how a selfie a photograph that one has taken of oneself typically one taken with a Smartphone or webcam and shared via social media is being used by some Late-capitalistic powers or some multinational companies organizations to promote the narcissistic idea of beauty in order to run their products in the market
Keywords: selfie; late- capitalistic; culture; narcissistic